ANALISIS KEBUTUHAN DESIGN REQUIREMENTS MODUL DIGITAL ENGLISH GRAMMAR BAGI MAHASISWA TEKNOLOGI REKAYASA PERANGKAT LUNAK - Sri Ariyanti Sabiku; Muchlis Polin; Jamal Darusalam Giu (Universitas Muhammadiyah Gorontalo, 2025)
The rapid advancement of digital technology requires English language instruction in vocational higher education to align with professional communication demands while addressing the characteristics of learners as users of digital learning media. However, the English Grammar teaching materials, particularly those covering verb tenses, used in the Applied Bachelor's Program in Software Engineering Technology at Universitas Negeri Gorontalo have not fully accommodated these two aspects. This study aimed to analyze learning needs by identifying target needs and learning needs from the perspective of English for Specific Purposes (ESP), together with user needs from the User-Centered Design (UCD) perspective, as the basis for developing a Design Requirements Specification for a digital English Grammar module. The study employed a descriptive qualitative approach, with needs analysis serving as the analytical framework integrating ESP and UCD perspectives. Data were collected from 29 first-year students through questionnaires, diagnostic assessments, and document analysis. The data were analyzed using descriptive statistics, interactive analysis, source triangulation, and requirements analysis and synthesis. The findings indicate that although students recognize the importance of verb tenses in software engineering communication, they continue to experience substantial competency gaps, particularly in the use of perfect tenses. Students also expressed the need for a digital learning module that is contextualized, interactive, supported by concept visualizations, provides immediate feedback, and is accessible via mobile devices. Integrating the findings from the ESP and UCD perspectives resulted in a Design Requirements Specification encompassing content, context, instructional, interface, interaction, and platform specifications, which serves as a conceptual foundation for the design and development of a digital English Grammar module in subsequent research.